Visibility and Analytics Network (VAN) approach to improve immunization supply chain and management performance system in Pakistan - Altaf, Arshad (J Glob Health, 2021)
BACKGROUND: Pakistan has been experiencing several immunization related challenges. The supply chain management information system (MIS) is considered an important component of immunization services as it can improve visibility in key areas such as vaccine shortages or wastage. This study assessed the effectiveness of the Visibility and Analytics Network (VAN) approach in improving vaccine supply and availability of stocks by comparing the situation in intervention and non-intervention districts in Sindh province of Pakistan. METHODS: We utilized a quantitative and qualitative approach to collect data to assess the VAN approach in two districts of Sindh province in Pakistan. The data were collected between August and October 2017. VAN is a systematic monitoring system which measures the performance of vaccine supply chain management based on a set of indicators. We assessed storage facilities of the Expanded Programme on Immunization (EPI) in Sindh and interviewed personnel involved using a pre-tested data collection tool. We also conducted in depth interviews with senior management to assess performance of VAN, adoption mechanism and needs to scale up the VAN approach. RESULTS: We assessed 52 EPI facilities of Sindh province government. In the intervention district 83.3% managers were using MIS data for decision making related to vaccine supplies whereas in the non- intervention district no MIS based data were available. Ninety percent of stores were maintaining a stock registry and 100% supplies matched with requisitions in the intervention district compared to 40% and 35% in the non-intervention district for the same variables. Vaccine wastage was high in the non- intervention district (BCG 46.7% vs 33.9; OPV 13.5% vs 9.5%; pneumococcal 11.4% vs 7.4%). In-depth interview findings suggested that the VAN approach provided data guided monitoring in Pakistan for the first time. The approach also enabled district managers to make timely decisions. CONCLUSION: The VAN approach improves vaccine supply chain management. It should be scaled up and implemented at national or sub national especially in countries struggling with vaccine supply chain management.